Using Online Short Stories to Improve the Reading Comprehension Ability - Syafii, Muhammad Lukman (Register Journal, 2018)
Abstract Reading materials can be obtained from many sources, like storybooks, magazines, and the Internet. Online Short Stories is one of the Internet resources with images and sound and quizzes. This study was aimed at benefiting these readily used materials to improve the eighth graders’ reading comprehension of narrative texts. The Online Short Stories are combined with five worksheets that consist of guiding questions on comprehension, namely: Self Monitoring Card, Key Concept, Story Map, Reading Journal, and Reading Log which are used for intensive and extensive reading activity. This study implemented classroom action research design and had taken 34 eighth graders of MTs Al-Islam Joresan Mlarak Ponorogo as the subjects 2017/2018 academic year. Based on the results of the students’ tests as well as their on-going assessments, it is found out that the students’ reading comprehension was gradually improving. It means that there was a positive effect of using Online Short Stories towards the students’ reading ability. The result shows that the combination of materials and worksheets that were implemented in both cooperative and individual learning had facilitated the students in improving their reading comprehension ability, as well as their social skills. Therefore, it is very important to implement this strategy to order to improve the students’ reading comprehension. Keywords: Online Short Stories, Improvement, Reading Comprehension Ability